THE EFFECT OF PROMOTION STRATEGIES, SERVICE QUALITY, ACCESSIBILITY, COLLECTIONS, AND DIGITIZATION ON LIBRARY VISIT RATES THROUGH THE MODERATION OF LIBRARIAN PERFORMANCE AT THE BANGKA REGENCY ARCHIVES AND LIBRARY OFFICE - Annisa Latifatin Nabila Zahra; Reniati Reniati; Hamsani Hamsani (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2026)
The current phenomenon is that public interest in reading is low, resulting in a decline in the public’s desire to return to the library. By leveraging librarians’ moderating role, this study aims to examine the impact of promotional strategies, service quality, accessibility, collection, and digitization on library visit rates at the Bangka Regency Archives and Library Service. A quantitative approach using the PLS-SEM analytical method was employed in this study. The study involved 97 participants. The findings indicate that promotion, service quality, and the collection have a significant impact on visits, whereas accessibility and digitization do not have a significant impact. Librarian performance, which moderates promotion strategies, service quality, and the collection, has a positive effect on visit rates but does not have a positive effect on accessibility and digitization. The number of library visitors is positively and significantly influenced by librarian performance. Based on the research findings, the Bangka Regency Archives and Library Office should focus on promotion strategies, service quality, collection development, as well as continuous training and guidance for librarian performance